Evolution and Deformability of Inclusions in Steel Containing Rare‐Earth Element Under Different Deoxidation Conditions. Issue 8 (21st May 2022) - Wang, Yeguang; Liu, Chengjun
Abstract : The experiments under different deoxidation conditions are carried out on the basis of thermodynamic calculation in the Ce–Si–Al–O–S system. The control conditions of various inclusions and the evolution of inclusions are investigated. The results show that Al2 O3 is modified to CeAlO3 by adding Ce, which is further transformed to Ce2 O2 S with the increase of Ce addition in Al‐killed melts. By adding Ce to the melts with Si and Si/Al deoxidation, SiO2 and SiO2 –Al2 O3 are gradually replaced by Ce2 SiO5 and SiO2 –Al2 O3 –Ce2 O3 liquid inclusions, respectively. Subsequently, the change of inclusions deformability at low temperature characterized by Young's modulus is calculated in Ce2 O3 –SiO2 –Al2 O3 oxide systems. The decrease of Al2 O3 content and the increase of Ce2 O3 and SiO2 contents improved inclusions deformability by reducing their Young's modulus. The inclusions deformability is improved by modifying SiO2 –Al2 O3 to SiO2 –Al2 O3 –Ce2 O3 inclusion. The Ce2 SiO5 with Young's modulus less than 160 Gpa shows good deformability among the RE‐inclusions in this study. Abstract : The evolution of inclusions in stainless steel under different deoxidation conditions with Ce addition is investigated. The inclusions deformability characterized by Young's modulus are evaluated in Ce2 O3 –SiO2 –Al2 O3 oxide systems. The deformability of inclusions in steel containing rare earth is expected to be controlled by the evolution of inclusions compositions.